Central Themes of the Pokémon Franchise and why they Appeal to Humans - Laato Samuli; Rauti Sampsa (United States, 2022)
Pokémon has become the most profitable cross-media franchise since its creation 25 years ago. In this conceptual work, we go through the current eight generations of Pokémon games, movies and anime episodes to understand why the franchise appeals to humans. We focus on the following four core themes: (1) relationship with the Pokémon creatures; (2) exploration and adventure; (3) social connectedness and acceptance; and (4) green technologies and living in symbiosis with the environment. We discuss how these themes resonate with human primal desires and what aspects of Pokémon transcend into the real world. Our findings indicate that the Pokémon world is able to offer humans aspects of the hunter-gatherer era that are missing from the current urban way of living. The franchise appeals to human primal desires by being about exploring the world, understanding it and finding harmony with other living creatures. Our findings support previous work on the appeal of specific Pokémon games, and contributes to our understanding of what has made the franchise popular.
Proceedings of the 54th Hawaii International Conference on System Sciences 2021